1
$\begingroup$

I found this questions from past year maths competition in my country, I've tried any possible way to find it, but it is just way too hard.

Given $$ \frac {x^2-y^2+2y-1}{y^2-x^2+2x-1} = 2$$ find $x-y$

I'm not sure if given choices is right... (A)2 (B)3 (C)4 (D)5 (E)6

I've tried to move them $$x^2-y^2+2y-1 = 2y^2-2x^2+4x-2$$ $$x^2-y^2+2y-1 - 2y^2+2x^2-4x+2 = 0$$ $$3x^2-3y^2+2y-4x+1=0$$ $$(3x-1)(x-1)-(3y-1)(y+1)+1=0$$

I've stuck in here, not sure if I've found x and y, or not...

EDIT: I've move other questions to other posts, thanks for helping me identifying the questions category.

$\endgroup$
  • 1
    $\begingroup$ lets try to keep it at one problem per post please. $\endgroup$ – Jorge Fernández Hidalgo Jul 25 '15 at 6:57
  • $\begingroup$ @dREaM i can't identify most of these question's category $\endgroup$ – wuiyang Jul 25 '15 at 7:01
  • 1
    $\begingroup$ Limiting to one question per question would help with your tagging woes, too :-) $\endgroup$ – Jyrki Lahtonen Jul 25 '15 at 7:04
  • 1
    $\begingroup$ @wuiyang All questions should have the tag contest-math. Furthermore 1,2,3,5,6,7 should have the tag algebra-precalculus. 4,8,9 should have the tag elemetary-number-theory. 7 should have the tag polynomials. $\endgroup$ – wythagoras Jul 25 '15 at 7:06
  • $\begingroup$ @wythagoras thanks, I will edit the questions now $\endgroup$ – wuiyang Jul 25 '15 at 7:10
4
$\begingroup$

Recognize the squares of binomials in both the numerator and denominator to rewrite the equation as $$\begin{align}\frac{x^2-(y-1)^2}{y^2-(x-1)^2} &= 2, \end{align}$$ and thus, factoring, $$\require\cancel \begin{align}\frac{(x-y+1)\cancel{(x+y-1)}}{(y-x+1)\cancel{(y+x-1)}}&=2. \end{align}$$ Finally, let $t=x-y$ and multiply both sides by $1-t$ to have $$\begin{align} t+1&=2(1-t) \\ 3t&=1 \\ t&=\frac{1}{3}. \end{align}$$

$\endgroup$
1
$\begingroup$

Put $t=x-y$ then $x=y+t.$ Substitute it into the expression you get $${\frac {t+1}{1-t}}=2.$$ By solving it you get $t=\dfrac{1}{3}.$

$\endgroup$
1
$\begingroup$

\begin{align} 2&= \frac {x^2-y^2+2y-1}{y^2-x^2+2x-1} \\ &=\frac {x^2-(y^2-2y+1)}{y^2-(x^2-2x+1)} \\ &= \frac {x^2-(y-1)^2}{y^2-(x-1)^2} \\ &= \frac {(x-y+1)(x+y-1)}{(y+x-1)(y-x+1)}\end{align} $$\implies {x-y+1}=2y-2x+2\\ 3(x-y)=1 $$

Thus, $x-y=\dfrac13$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.